Cost X-efficiency in China's banking sector: Comparison of domestic and locally incorporated foreign banks - ZHANG, ZEDONG (2015)
This study estimates and compares the cost X-efficiency levels of domestic and locally incorporated foreign banks in China’s banking system with the data of banks headquartered in 14 different cities over the period of 2009-2013. Stochastic frontier approach (SFA) is adopted to estimate the X-efficiency level of each bank in the sample. The findings suggest that domestic banks are a little more efficient than locally incorporated foreign banks and the cause of efficiency difference comes mainly from the exogenous factors instead of the management diversity.